DIALOG OF INTERFAITH AND INTERBELIEF COMMUNITIES OF PANTURA (TALI AKRAP): AN OVERVIEW FROM THE STRUCTURAL FUNCTIONAL THEORY - Ama Farida Sari; Rusnaini Rusnaini; Triana Rejekiningsih (Analisa: Journal of Social Science and Religion, 2019)
Interfaith dialog is commonly carried out to harmonize the relationship and minimize conflicts between religious believers. This study examines how the functional structure of an interfaith community and beliefs can create harmonious interfaith relationship through an interfaith dialog held in Kudus, Central Java. This study is designed with qualitative research model by applying the phenomenological approach. The data were technically collected through interviews, observation, document studies and Focus Group Discussion (FGD). Theoretically, this study used Talcott Parsons’ structural functional theory. The results showed that the Interfaith and Interbelief Communities of Pantura (TALI AKRAP) is a system in society where the religious adherents and the flow of beliefs are the integrated elements, each of which should function one another in creating a balance in society. As a system, TALI AKRAP holds four imperative functions which are simultaneously integrated in action systems, namely adaptation, goal attention, integration and learn pattern maintenance or commonly abbreviated AGIL. The existence of adaptation between religious adherents in the community aims to understand, recognize and accept one another as an effort to realize the harmony among religious believers. The goal to be achieved is a community with concern, tolerance, lives side by side and accepts differences as a gift from the God Almighty, all of which are integrated in social dialog activities between religious believers which exist for a long time and are carried out continuously.